STRATEGI GURU DALAM MENGATASI RENDAHNYA HASIL BELAJAR EKONOMI SISWA DI SMA NEGERI 2 BANJAR - Komang meitri Paramitha (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to analyze teachers' strategies in overcoming low student learning outcomes in economics at SMA Negeri 2 Banjar. The study uses a descriptive qualitative approach with economics teachers as subjects. Data were collected through focused interviews and learning documentation. The results of the study show that the average economic score of students is 64 with a minimum passing grade of 75. The learning completeness rate reaches 40 percent, while 60 percent of students have not yet completed the course. The learning completeness rate reaches 40 percent, while 60 percent of students have not completed the learning. These findings indicate that students' learning outcomes in economics are still low. The interview results show that economics learning is still dominated by a teacher-centered approach, which has an impact on the low level of student activity and understanding of concepts. Teachers began to apply a variety of learning strategies such as trigger questions, group discussions, and the use of contextual economic case studies, but their application was not consistent. The main obstacles faced include limited learning time, passive learning habits among students, differences in motivation and readiness to learn, and limited learning resources. Teachers' efforts are carried out through learning reflection, adjusting methods to classroom conditions, more focused time management, and the use of evaluation as a basis for learning sharing. The research findings confirm that teacher strategies play an important role in improving the quality of the economics learning process, but require consistency in implementation and support for learning conditions so that student learning outcomes can be maximized